1949
DOI: 10.2508/chikusan.20.123
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the artificial insemination in horses

Abstract: Studieson the artificial insemination in horses. III.A new preservation method of the horse spermatozoa, so-called Baken method Y. NISHIKAWA Y. WAIOE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Regarding gonadal development, the EP treatment promoted gonadal function in colts and fillies reared in Hidaka and fillies in Miyazaki. An increase in testicular hormone secretion was noted in colts, and promotion of follicular growth and advancement of ovulation were noted in fillies, clarifying that EP treatment promotes gonadal function in yearling fillies in a manner similar to broodmares [ 7 , 23 , 53 ]. No effect of the EP treatment on growth and gonadal function was noted in colts reared in Miyazaki, and the reason for this is unclear at this point.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gonadal development, the EP treatment promoted gonadal function in colts and fillies reared in Hidaka and fillies in Miyazaki. An increase in testicular hormone secretion was noted in colts, and promotion of follicular growth and advancement of ovulation were noted in fillies, clarifying that EP treatment promotes gonadal function in yearling fillies in a manner similar to broodmares [ 7 , 23 , 53 ]. No effect of the EP treatment on growth and gonadal function was noted in colts reared in Miyazaki, and the reason for this is unclear at this point.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing the characteristic of horses that they are long-day seasonal breeders, EP treatment has been performed to advance ovulation in broodmares [ 10 , 16 , 37 , 40 , 43 ]. In the present study, the effect of EP treatment on the gonads and hair coat in Thoroughbred yearlings were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…EP treatment advanced elevation of circulating prolactin in both colts and fillies. Previous papers reported that molting of winter hair coat was stimulated by long-day EP treatment [ 31 , 40 , 43 ], administration of prolactin [ 50 , 51 ] or sulpiride, antagonist of dopamine, [ 14 , 50 , 51 ] in horses. The present study clearly demonstrated that the early elevation of circulating prolactin observed in both colts and fillies was promoted by EP treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations